Understanding Nanostructuring Processes in Thermoelectrics and Their Effects on Lattice Thermal Conductivity - Wu, Di (Advanced materials (Deerfield Beach, Fla.), 2016)
© 2016 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.